Transoesophageal Echocardiography in Anaesthesia and Intensive Care Medicine. - Poelaert, Jan (John Wiley & Sons, 2007)
Transoesophageal Echocardiography (TOE) has a major impact on patient management during the perioperative period. It is an evolving tool in diagnosis of cardiovascular disease and haemodynamic assessment. The knowledge required for the examination and the practice of TOE is enormous and is continuously evolving. Consequently there is a clear need for a new comprehensive text written by experts involved in the perioperative care, not (only) by the cardiologists or full time echocardiographers.